Detection of Newcastle disease virus in edible-nest swiftlet (Aerodramus fuciphagus) ranched under an oil palm plantation in Sungkai, Perak, Malaysia - Chow, Guo Hao; Abu, Jalila; Arshad, Siti Suri; Tan, Sheau Wei; Muhamad, Siti Khatijah; Ong, Kang Woei (2012)
Newcastle Disease is regarded as one of the most important disease of avian species and was listed as ‘A’ disease by the Office International des Epizooties (OIE). Studies have shown this disease infects more than 250 species of birds. The edible-nest swiftlet industry in Malaysia is on the rise for the last 10 years and swiftlet houses can be seen everywhere. This is due to the high price of edible bird nests at international market and high income generated by the farming of edible bird nest. Nevertheless, edible-nest swiftlet (Aerodramus fuciphagus) is can either be infected with or carrying the deadly Newcastle disease virus (NDV) which is a great threat to the poultry industry in this country. In Peninsular Malaysia, no study on this subject was reported so far in this swiflet species. In this study, 60 swiftlet carcasses were sampled. Post-mortem was conducted and lung and trachea tissues were collected. Tissue samples were tested for NDV using the reverse-transcriptase polymerase chain reaction (RT-PCR). Newcastle Disease Virus was not detected in any of the samples. Thus, it can be concluded that edible nest swiftlets (Aerodramus fuciphagus) ranched under oil palm plantation in this study are not infected with or carry NDV.